Capturing Doughnut Economy Concept in Bali - PUTRA, I Komang; PRAMARTHA, I Made Aditya; CATURYARTA, Anak Agung Putu Agung (Journal of Tourism Economics and Policy, 2025)
This study aims to examine the community's understanding of the concept of donut economy and explore its potential application in the social and economic context in Bali Province. With a focus on equitable and sustainable development, this research is expected to provide an empirical basis in formulating local economic transition strategies that are in accordance with the principles of the donut economy. The method used in this research is a descriptive-analytical approach with primary data collection through a survey using questionnaires to communities and stakeholders in Bali. The data will be strengthened by literature review and content analysis of scientific journals, policy reports, and case studies from other relevant regions. The results show that the interaction relationship of understanding the concept of doughnut economy with the support of Balinese traditional culture has a positive effect on the potential application of doughnut economy while the variables of perceived social needs and ecological awareness have not shown a significant effect, either directly or through moderation of Balinese traditional cultural support. This finding indicates that the potential of doughnut economy implementation in Bali is strongly influenced by the extent to which its principles can be integrated into local cultural values, norms and practices.